Some considerations about several roads from Moesia reflected in “itineraria picta et adnotata” - FODOREAN, Florin–Gheorghe (Studia Universitatis Babeș-Bolyai Historia, 2016)
Several years ago, in 2011, I started a research focused on some of the most important cartographic documents of the Roman world: the Peutinger map and the Antonine itinerary. The idea for this research started from several fundamental questions: 1. Do the Peutinger map and the Antonine itinerary offer different information related to the roads of the Roman provinces? 2. How can one establish this? 3. How did other late sources, such as the Notitia Dignitatum, the Bordeaux itinerary, or the Cosmography of the Anonymous from Ravenna, present or describe these regions? 4. How were the Peutinger map and the Antonine itinerary actually compiled? 5. By analyzing the routes of these provinces, can one obtain new information useful to dating the above-metioned documents? 6. So far, in order to date these documents, historians have discussed them as a whole or separately, focusing on small, sometimes insignificant details from certain areas. What other methodological criteria or means can be employed, beside the classical, established methods, to provide new data? 7. Can we differentiate between the purpose of the Peutinger map and the Antonine itinerary? 8. Supposing that new dating criteria can be identified, will they be useful for further research and could this method be applied to other regions, and finally to all former Roman provinces? 9. The Peutinger map and the Antonine itinerary each list around 2700 settlements. Can one compare these two documents by analyzing the presence or the absence of certain settlements, in order to date the documents? To find possible new insights, I have compared the distances between the settlements, and I have chosen to discuss the situation from Moesia. Rezumat: Acum câţiva ani, în 2011, am început o cercetare legată de cele mai importante documente cartografice ale lumii romane: Tabula Peutingeriana şi Itinerarium Antonini. Ideea aceastei cercetări a început de la câteva întrebări fundamentale: 1. Cele două documente amintite oferă informaţii diferite privind drumurile din provinciile romane? 2. Cum putem stabili acest lucru? 3. Cum au fost descrise aceste drumuri în alte surse romane târzii, precum Notitia Dignitatum, itinerariul de la Bordeaux sau Cosmographia Anonimului din Ravenna? 4. Cum au fost redactate Tabula Peutingeriana şi Itinerarium Antonini? 5. Prin compararea drumurilor din anumite provincii, se pot obţine informaţii noi utile în datarea celor două documente? 6. Până în prezent, pentru a data cele două documente, istoricii le-au discutat fie în ansamblu, fie separat, concentrându-se uneori pe detalii prea mici, nesemnificative din anumite zone. Ce alte criterii metodologice sau mijloace pot fi utilizate, în afară de metodele clasice stabilite, pentru a obţine noi date? 7. Se poate face o distincţie între scopul Tabulei şi cel al documentului Itinerarium Antonini? 8. Presupunând că pot fi identificate noi criterii de datare, pot fi aceastea utile pentru viitoare cercetări, şi poate fi această metodă aplicată şi pentru alte regiuni, şi în final pentru toate provinciile romane? 9. Atât Tabula Peutingeriana, cât şi Itinerarium Antonini, amintesc fiecare în jur de 2700 de aşezări. Pot fi comparate cele două documente prin analiza prezenţei sau absenţei anumitor localităţi, pentru a data aceste documente? Pentru a descoperi noi informaţii, am comparat distanţele dintre aşezări, şi am decis să discut situaţia din Moesia. Cuvinte cheie: Imperiul Roman, cartografie, Tabula Peutingeriana, itineraria, Moesia